POTENCY OF AMINO ACIDS AS SAVORY FRACTION FROM VEGETABLE BROTH OF MUNG BEANS (Phaseolus radiatus L.) THROUGH BRINE FERMENTATION BY Rhizopus-C1 - Agustine Susilowati; Aspiyanto Aspiyanto; Sri Moerniati; Yati Maryati (Universitas Gadjah Mada, 2009)
Amino acids produced through brine fermentation of mung beans (Phaseolus radiatus sp) by inoculum of Rhizopus-C1 at room temperature for 0, 2, 4, 6, 8, 10, and 12 weeks, respectively had a potential use as savory fraction for seasoning agent. The objective of this experiment was to find out characteristic of produced amino acids and composition of fermentation products relating with proteolitic and amylolitic activities of Rhizopus-C1. The result of experiment showed that the length of fermentation time would increase intensity of savory taste and cloudy color, and increase total protein, soluble protein, and N-amino concentrations, decrease water, while fat concentration was constant. Fermentation of 10 weeks was optimal time to get crude broth with concentrations of total protein of 9.5622%, soluble protein of 8.5 mg/g, N-amino of 5.6 mg/g, fat of 0.2802%, water of 40.7189%, Volatile Reduction Substances (VRS) of 90 µeq/g, and reduction sugar of 672.5 mg/mL. Kinds of dominant non-essential amino acids produced were glutamic acid (1.014%), and aspartic acid (0.507 %), while essential amino acids were lysine (0.474%), and isoleucine (0.644%). The other of amino acids were resulted with concentration of 0.211 - 0.345%, such as leucine, arginine, serine, glycine, histidine, alanine, proline, tyrosine, valine, methionine, cystine, threonine, and phenilalanine. Visually, crude vegetable broth produced through brine fermentation of mung beans by Rhizopus sp-C1 was semi solid, brownish color, rather fatty, salty, and enough strong savory taste.